2012
DOI: 10.1155/2012/507278
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Methylsulfonylmethane on Hemodynamics and Oxidative Stress in Monocrotaline-Induced Pulmonary Hypertensive Rats

Abstract: Methylsulfonylmethane (MSM) is naturally occurring organic sulfur that is known as a potent antioxidant/anti-inflammatory compound. The aim of this study was to investigate the effect of MSM on hemodynamics functions and oxidative stress in rats with monocrotaline- (MCT-) induced pulmonary arterial hypertension (PAH). Wistar rats were randomly assigned to 38-days treatment. MSM was administered to rats at 100, 200, and 400 mg/kg/day doses 10 days before a single dose of 60 mg/kg, IP, MCT. Hemodynamics of ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 22 publications
4
17
0
1
Order By: Relevance
“…), and the right ventricular systolic pressure (RVSP) and heart rate (HR) were measured by PowerLab (AD Instruments) (Mohammadi et al. ). After the needle penetrated the intraventricular septum, the left ventricular systolic pressure (LVSP) was measured.…”
Section: Methodsmentioning
confidence: 99%
“…), and the right ventricular systolic pressure (RVSP) and heart rate (HR) were measured by PowerLab (AD Instruments) (Mohammadi et al. ). After the needle penetrated the intraventricular septum, the left ventricular systolic pressure (LVSP) was measured.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, oxidative stress has been indicated as a major contributor in the development of PH, suggesting that antioxidant therapy may be considered as a successful therapy against the disease [17][18][19][20][21][22][23]. Melatonin is a powerful antioxidant which can limit damage in cardiovascular disease [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant enzyme activities in MCT-induced heart failure seem to differ with respect to the cellular type and compartment, and the results of various studies have been conflicting. Thus, Mohammadi et al (2012) found that levels of extracellular SOD and GSH-Px in MCT-treated rats were significantly decreased 4 weeks after treatment. Similar downregulation in antioxidant enzymes in MCT-induced heart failure was also found in soleus (oxidative and slow-twitching muscle) muscle tissue (Bertaglia et al 2011).…”
Section: Discussionmentioning
confidence: 87%